Assessing The Influence of Board of Commissioners, Audit Committees, and Company Scale on Business Performance - Lasmi, Ni Wayan; P, Komang Widhya Sedana Putra; Sukarnasih, Desak Made (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
In this study, experts aimed to identify variables influencing organizational performance, focusing on the size of the audit committee and the composition of the board of commissioners as two indicators of corporate governance (GCG). These variables are crucial for achieving organizational goals and implementing effective GCG practices. The Board of Commissioners, working closely with the organization, oversees internal operations, with the Audit Committee assisting in fulfilling its responsibilities. The Audit Committee is responsible for financial reporting, internal auditing, and ensuring GCG compliance. Company size and performance are closely linked, with larger organizations often performing better in operational activities. This study investigates the impact of company size, the board of commissioners, and the audit committee on business performance. Utilizing data from annual financial reports of the food and beverage subsector for the years 2020-2022, sourced from the official IDX website, the study analyzed 99 samples using multiple regression analyses. The findings shed light on how organizational performance is influenced by company size, the audit committee's composition, and the board of commissioners.